PERANAN STRUKTUR MODAL, CSR, DAN PERTUMBUHAN PENJUALAN BAGI NILAI PERUSAHAAN - Kusnadi, Sal-Sabilla Narita; Haryati, Tantina (Distribusi - Journal of Management and Business, 2025)
The mission of this research is to conduct an evaluation and assessment of the effects of firm size on the impact of capital structure, sales growth, and CSR on firm value. This research employs a quantitative methodology. Utilizing a purposive sampling approach, the research sample consisted of 26 companies out of a total population of 84 food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the period of 2018 to 2022. Partial Least Square (PLS) was employed in the data analysis process with the assistance of SmartPLS 3.0 software. The secondary data used in this research was obtain from annual reports sourced from the official IDX and company websites. The research findings indicate that an increase in sales didn't impact on firm value, while capital structure and CSR have a positive and significant impact on it. Moreover, firm size weakens the impact of capital structure on firm value and fails to influence the effects of sales growth and CSR.